The relationship between different temperaments and postpartum depression in health centers in Sabzevar, 2017 - Marzieh Torkmannejad Sabzevari; Mitra Eftekhar Yazdi; Sedighe Rastaghi; Mostafa Rad (Mashhad University of Medical Sciences, 2018)
ntroduction: Postpartum depression is one of the most common disorders associated with various factors. Considering the level of hormones in different temperaments, this study was conducted to determine the relationship between cold and hot temperaments and postpartum depression. Methods: This descriptive and analytic study was conducted on 169 primi- and multiparous women in Sabzevar, Iran, in 2017. The temperament questionnaire was completed before delivery and the Edinburgh Depression Inventory was completed at the nearest health center in the third or fourth postpartum weeks. To analyze the data, logistic regression test was performed in SPSS, version 20. P-value less than 0.05 was considered significant. Results: Chi-square test showed a significant correlation between cold and warm temperaments and postpartum depression (P = 0.001). Out of 48 cold-tempered participants 46 (95.8%) had postpartum depression. Depression rate was the lowest in moderate temperament (17.9%). Logistic regression test showed a significant relationship between postpartum depression and cold and warm temperaments (P <0.05). Conclusion: During the post-partum period, those who have a cold temperament are more likely to suffer from depression than those who are warm tempered. It is suggested that obstetricians and midwives should follow mothers' postpartum depression according to the type of temperament.